Leptin/Melanocortin pathway hormones in obese patients after laparoscopic sleeve gastrectomy - Tas, A.; Atabey, M.; Gokcen, P.; Ozel, M., I; Karagoz, Z. K.; Ugur, K.; Silig, Y. (Verduci Publisher, 2022)
OBJECTIVE: The melanocortin system is an important neural system underlying the control of body weight and food intake. This system has recently received great attention as a potential target for obesity treatment. There-fore, the objective of this study was to find out the leptin-melanocortin pathway before and after Laparoscopic Sleeve Gastrectomy (LSG) in obese patients. PATIENTS AND METHODS: The study was carried out with a total of 144 individuals in 3 groups [control, obese group before LSG and obese group after LSG (who underwent LSG one year ago)]. The amount of leptin (LEP), leptin receptor (LEPR), tropomyosin receptor kinase receptor B (TrkB), brain-derived neurotrophic factor (BDNF), pro-opiomelanocortin (POMC) and melanocortin-4 receptors (MC4R) molecules were measured by using Enzyme-Linked Immunosorbent Assays. RESULTS: A statistically significant difference was found between the groups in terms of body mass index (BMI) values (p = 0.001). There was also statistically significant difference present between obese before LSG group and obese after LSG group regarding the levels of LEP, TrkB, BDNF and proteins (p < 0.05). A decline was determined in the LEP and BDNF levels one year followup after LSG. CONCLUSIONS: The evidence suggests that the leptin melanocortin pathway strictly regulates food intake and BMI before and after LSG surgery. This pathway should be kept under control for effectively reducing food intake and body weight in the treatment of obesity.
Keywords: Obesity; Leptin; melanocortin pathway; Leptin; LEPR; TrkB; BDNF; POMC; MC4R; Laparoscopic sleeve gastrectomy